(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article is devoted to the continuity of architectural traditions reflected in the miniature of two great eras - the Temurids in Central Asia and the Baburids in northern India. The traditions of their architecture and fine arts continued and multiplied, making a huge contribution not only to the development of the cultural heritage of the two countries, but also became the property of the world heritage of all mankind, which must be preserved for future generations.